Quantum identity authentication for non-entanglement multiparty communication: A review, state of art and future directions - Azahari, Nur Shahirah; Harun, Nur Ziadah; Ahmad Zukarnain, Zuriati (Korean Institute of Communications and Information Sciences, 2023)
Authentication is one of the security services that assures the system’s adequate security through identification and verification. Additionally, it guarantees that the communication party is who they claim to be. In politics, the economy, banking, daily life, and other areas, quantum identity authentication is essential to guarantee the security of information in communication. The multiphoton strategy is an improved version of the single-photon approach, with higher transmission rates and longer photon travel distances via the Quantum Communication network. Despite the advantages of multiphoton, enforcing authentication on behalf of numerous participants in the quantum channel remains a problem, since existing multiphoton only considers two parties involved in secret message sharing. The issue of scalability arises here when the number of parties involved in the quantum network increases. Furthermore, an eavesdropper might hide her position among other parties and take advantage of the situation to obtain a certain information. Therefore, we require a protocol, that creates a more secure environment in term of authentication in which multiple parties may freely and openly communicate. This paper further identifies research gaps covering critical aspect on how Quantum Identity Authentication (QIA) can be realized and effectively utilized for multiphoton without entanglement based. These include suggestion of future direction to implement multiphoton in multiparty from current protocol.